Clinical, cytological and microbiological evaluation of bronchoalveolar lavage in children: A referral hospital-based study. (November 2016) - Pourakbari, Babak; Mahmoudi, Shima; Jafari, Amir Hossein; Bahador, Abbas; Keshavarz Valian, Sepideh; Hosseinpour Sadeghi, Reihaneh; Mamishi, Setareh
Abstract: Introduction: Diffuse lung diseases (DLD) in children involve a group of heterogeneous, rare disorders. In spite of the low diagnostic yield in pediatric DLD, bronchoalveolar lavage (BAL) can be used to diagnose specific disorders. There are few studies about microbial and cellular profiles of BAL samples in these patients. This study was conducted to evaluate the clinical, cytological and microbiological evaluation of BAL in children with DLD. Methods: The clinical, cytological and microbiological profiles of BAL samples of all patients with DLD who underwent the fiberoptic bronchoscopy (FOB) at Children's Medical Center, an Iranian referral pediatrics Hospital during a year were evaluated. Results: In 18 patients (18.4%) of the 98 cases studied, 22 pathogens were obtained as etiologic agents. The mean total cells count of BAL was 23.9 × 104 ± 12.9 × 104/ml. The mean percentages of cellular components were macrophages (70.2%), neutrophils (16.3%), lymphocytes (11.8%) and eosinophils (1.4%), respectively. The type of lung disease was significantly associated with the mean percentage of lymphocytes (p = 0.005) and the percentage of neutrophils (p = 0.042). Conclusion: FOB and BAL evaluation in combination with clinical and radiographic imaging data may be helpful for identifying of presumptive diagnosis of DLD in children. Highlights: In 18.4% patients, bronchoscopic images have been helpful in determining the etiology of diseases. BAL evaluation led to isolate the etiologic agents of lower respiratory tract infection in 16.7% of patients (35 bacteria, 14 viruses and 7 fungi including 5 P. carini ). Fourteen out of the 22 microbial microorganisms obtained from BAL samples were reported from patients with immune deficiency. BAL data as a diagnostic tool should be used in combination with the clinical and radiological findings. A biopsy of the lung should be considered as a last step if the diagnosis of DLD remains unclear.